The Learning Model of Physical Education Locomotor Basic Learning in Grade III Primary School - Nandasari, Eka; Pujianto, Agus; Harsono, Tri Nur (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this study is to produce games letter word in the learning of basic locomotor movements physical education at Elementary School third-grade students in District Gunungpati 2016. This research is the development, product development procedure includes needs analysis, literature review and observation, the initial product manufacturing, design validation by the experts, the trials I, product revision, the second large-scale trials, expert review and the final product. Data is collected using questionnaires obtained from the expert evaluation, field observations and the student questionnaire. A descriptive data analysis techniques percentage. The results of the analysis of the initial product of 91% then declared eligible. The observation and the student questionnaire on a small scale trial gained (81.6%). The test results of large-scale expert (95%) to be eligible and could be used. The observation and questionnaire on large-scale test was (86.6%) are feasible and can be used. On a small scale trials and large-scale increase in the observation and questionnaires to students of (5%). It can be concluded that the game is a good letter word that is feasible and can be used as an alternative to the basic motion locomotor learning materials in elementary school third-grade students in District Gunungpati.